Mushrooms of the pleurotus genus: A review of cultivation techniques - Carvalho, Cristiane Suely Melo de; Sales-campos, Ceci; Andrade, Meire Cristina Nogueira de (Interciência, 2010)
The cultivation of edible mushrooms in agro-industrial residues is considered a millennial activity, spread and practiced all around the world. Besides their excellent taste, edible mushrooms have a great biotechnological potential, due to their capacity to produce enzymes and medicines, to act in bioremediation, and other uses. The goal of the present work was to carry out a bibliographic review of the different cultivation techniques used in the production of Pleurotus spp. A wide variety of residues may be used as substrate in the cultivation of this mushroom. The use of agro-industrial byproducts represents an economically viable and very promising alternative for small producers, due to the low aggregate value and great availability.
Keywords: Basidiomycota; Pleurotus